Gender Differences in Cognition in China and Reasons for Change over Time: Evidence from CHARLS - Xiaoyan Lei; James P. Smith; Xiaoting Sun; Yaohui Zhao (Institute for the Study of Labor (IZA), 2013)
In this paper, we model gender differences in cognitive ability in China using a new sample of middle-aged and older Chinese respondents. Modeled after the American Health and Retirement Survey (HRS), CHARLS respondents are 45 years and older and are nationally representative of the Chinese population in this age span. Our measures of cognition in CHARLS relies on two measures that proxy for different dimensions of adult cognition - episodic memory and intact mental status. We relate these cognitive measures to adult health and SES outcomes during the adult years. We find large cognitive differences to the detriment of women that were mitigated by large gender differences in education among these generations of Chinese people. These gender differences in cognition are especially concentrated in the older age groups and poorer communities within the sample. We also investigated historical, geographical, and cultural characteristics of communities to understand how they impact cognition. Economic development and environmental improvement such as having electricity, increase in wage per capita and green coverage ratio generally contribute to higher cognition ability. Women benefit more from the fruits of development - electricity and growth of green coverage ratio are conducive to lessening female disadvantage in cognition.
Keywords: H10; 330; China; cognition